Constructing a DNA profile frequency database for South Africa using the Qiagen Investigator 24plex GO! Kit - Nel, Lorraine (Division of Forensic Medicine and Toxicology, 2018)
DNA profiling is routinely used in the forensic setting to identify individuals during criminal and medico-legal investigations. Its principle is based on the molecular analysis of DNA to produce a string of alpha-numeric characters which can be matched to a known reference sample. The use of allele frequencies from the background population aids the statistical interpretation of a match and can be used to calculate the random match probability. In South Africa, allele frequency data for the background population is currently limited, which can hinder the discriminatory value of DNA evidence, particularly when only a partial profile is obtained. Therefore, the aim of this study was to generate DNA allele frequency data for four South African population groups using the QIAGEN Investigator® 24PLEX GO! Kit, which has six markers for which data does not yet exist for the South African population. Full forensic DNA profiles were generated from 655 unrelated individuals from four population groups in South Africa: Black African (n = 172), Coloured (n = 195), Indian/Asian (n = 88) and White (n = 200). A 98% first time success rate was observed using the direct PCR approach. Allele frequencies were significantly different between all four population groups at three markers (D8S1179, D2S1338 and D2S441) after a Bonferroni correction (ρ < 0.001) and sixteen novel alleles were observed. Two genetic anomalies were observed, namely triallelic patterns at the TPOX marker (n = 9) and a null allele at amelogenin (n = 1). While the sample size for the Indian/Asian population group was limited in this study, the data generated here nevertheless prospects to contribute towards the data currently published for South Africa. This, in turn, will allow for more DNA markers to be analysed during forensic casework in South Africa, as the data for its statistical interpretation is now available.